2021
DOI: 10.48550/arxiv.2105.06959
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Many-body theory of positron binding in polyatomic molecules

Abstract: Positrons bind to molecules leading to vibrational excitation and spectacularly enhanced annihilation. 1 Whilst positron binding energies have been measured via resonant annihilation spectra for ∼ 80 molecules in the past two decades, [2][3][4][5][6][7][8][9][10][11][12] an accurate ab initio theoretical description has remained elusive. Of the molecules studied experimentally, calculations exist for only 6, and for these, standard quantum chemistry approaches have proved severely deficient, agreeing with expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 85 publications
(104 reference statements)
0
7
0
Order By: Relevance
“…These calculations showed that more compact molecular structures generally have higher ε B values. The ab initio many-body calculations of reference [4] observe a similar dependence on the shape of the molecule. In the framework of reference [4], the 'geometrical effect' described here also has contributions due to the differences in the individual molecular orbitals, including their individual ionization energies and other properties such as the anisotropic polarizability.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…These calculations showed that more compact molecular structures generally have higher ε B values. The ab initio many-body calculations of reference [4] observe a similar dependence on the shape of the molecule. In the framework of reference [4], the 'geometrical effect' described here also has contributions due to the differences in the individual molecular orbitals, including their individual ionization energies and other properties such as the anisotropic polarizability.…”
Section: Discussionmentioning
confidence: 62%
“…It was hypothesized that this could be due to virtual positronium. The important role of virtual positronium has also been quantitatively determined in recent ab initio many-body calculations of positron-molecule binding energy [4]. In the latter description, many-body techniques are used to calculate the positron-electron correlation energy, including the effect of virtual positronium.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations